PENGARUH HARGA, E-PROMOSI DAN KEPERCAYAAN, TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE DI APLIKASI LAZADA (Studi Kasus Pada Mahasiswa Universitas Satya Negara Indonesia Kampus A) - Fitriati Oktavani; Lucy Nancy Simatupang (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2020)
This research aims to determine the impact of price, e-promotion, and trust on purchasing decisions online in the Lazada app. The method used in this research is the quantitative method and assessment of the results based on respondents ' answers using a Likert scale. The population in this study is of Satya Negara Indonesia University student A the samples in this study amounted to 86. The data analysis methods used in the study are test linear regression test Multiple, F-Test, T-Test, and coefficient of determinant. The results showed that simultaneously (test F) showed that there was a significant influence between the price variables (X1), the e-promotion (X2), and the trust (X3) against the purchase decision (Y). Partial (T-Test) the price is influential as significant to the purchase decision, and the e-promotion is influential as significant to Purchase decision. whereas the trust variable does not influential as significant to the purchase decision.